Modelling and experimental characterisation of the rate dependent fracture properties of gelatine gels. (April 2015) - Forte, A.E.; D'Amico, F.; Charalambides, M.N.; Dini, D.; Williams, J.G.
Abstract: The mechanical behaviour of gelatine gels as a function of test rate and gelatine concentration was determined through lubricated uniaxial compression and wire cutting tests. Similar to other reported literature, it was observed that the fracture stress and strain of the gels were strongly strain rate dependent whereas the strain rate effect was insignificant on the deformation/stiffness properties. The wire cutting tests led to values of energy release rate, G c, being determined as a function of cutting rate. It was found that at small rates (up to 10 mm/min), the value of G c for the 10% w/w gelatine concentration was constant at an approximate value of 1.1 J/m 2 . For higher values of test rate, G c increased such that the log G c versus log cutting rate data were well approximated with a line of slope equal to 0.5. An analytical model describing this behaviour is suggested which takes into account the fluid flow of the water through the polymeric porous gel structure. In addition, a numerical simulation of the uniaxial compression was performed using a poroelastic material model. The model enabled the effect of the strain rate on the stress in the solid network and the pore pressure to be determined. A failure criterion based on maximum solid stress was suggested which led to a reasonable agreement with the experimental failure stress and strain data as a function of strain rate. Graphical abstract: Highlights: Strain rate markedly affects fracture of gelatine gel whereas modulus does not depend on strain rate. Analytical wire cutting model predicted power law dependence ( n = 0.5) of fracture toughness on cutting rate. Numerical simulation quantified solid stress and pore pressure contributions. A critical maximum solid stress fracture criterion predicted observed strain rate dependence.